A small podocnemidoid (Pleurodira, Pelomedusoides) from the Late Cretaceous of Brazil, and the innervation and carotid circulation of side‐necked turtles. (12th February 2020) - Hermanson, Guilherme; Iori, Fabiano V.; Evers, Serjoscha W.; Langer, Max C.; Ferreira, Gabriel S.
Abstract: Pleurodires are less diverse than cryptodires, together forming the two major lineages of crown turtles. Their fossil record, however, is rich. A particularly large number of fossil pleurodires, many belonging to the Podocnemidoidae, has been recovered from the Upper Cretaceous Bauru Group outcrops of south‐central Brazil. Herein we describe an additional pleurodire from this region, Amabilis uchoensis gen. et sp. nov., based on a partially preserved skull. A. uchoensis is recognized as belonging to the Podocnemidoidae by the small entrance to the antrum postoticum and completely developed cavum pterygoidei, being unique among other non‐podocnemidid podocnemidoids for its medially open fenestra postotica and absent basioccipital–opisthotic contact. Our cladistic analysis places A. uchoensis as a sister taxon to Hamadachelys  + other podocnemidoids. We further explore the neuroanatomy of side‐necked turtles with the aid of micro‐computed tomography of specimens of the main pleurodiran lineages. Our data shed light on the different carotid circulation patterns in pleurodires, and we propose new phylogenetic characters to describe the neuroanatomical variation of the group. Optimization of these characters shows two independent acquisitions of a foramen for the palatal branch of the carotid in chelids and podocnemidoids, and a unique loss of the vidian nerve canal in chelids, in turtles in general.